Analyzing the Impact of Dissolved Organic Components on River Water Quality and Its Implications for Human Health: A Case Study from Banjar District - Zubaidah, Tien; Hamzani, Sulaiman; Arifin, Arifin (JURNAL KESEHATAN LINGKUNGAN, 2024)
Introduction: Environmental contamination, especially water quality, is a global issue. The association between river water quality and human health is explored in Banjar Regency, rich in natural resources and essential rivers, utilizing dissolved organic components concentration as an indicator. Methods: A mixed-methods study in Banjar District, South Kalimantan, Indonesia, examined the impact of river water quality on human health, using dissolved forganic components as a primary indicator. Water quality assessments, nutrient content measurements, consumption surveys, and water-related disease epidemiology provided data. The statistical studies revealed key correlations and patterns. Results and Discussion: Water quality metrics varied among sampling locations. The dissolved fish feed negatively correlated with dissolved oxygen, while nutrient content weakly correlated with gastrointestinal disorders. High water temperatures increased respiratory illnesses. Drinking water from sources with high dissolved fish feed content caused digestive and respiratory problems. The study confirms previous research linking water quality parameters to health effects. The complex relationship between water quality and health is location-dependent, illustrating how environmental factors, especially water quality, shape illness trends. Conclusion: The study illuminates the complex links between river water quality, human health, and water usage in Banjar District. Dissolved fish feed content affects digestive and respiratory disorders, emphasizing the need of water quality management for regional health. These findings guide Banjar District water resource management and public health measures and help solve worldwide environmental pollution issues.